Respuesta :

[tex]$\frac{(x+1)(x-3)}{x^{2}}[/tex]

Solution:

Given expression:

[tex]$\frac{\frac{36}{x^{2}}+\frac{36}{x}}{\frac{36}{x-3}}[/tex]

To solve this expression:

[tex]$\frac{\frac{36}{x^{2}}+\frac{36}{x}}{\frac{36}{x-3}}[/tex]

Apply the fraction rule: [tex]$\frac{a}{\frac{b}{c}}=\frac{a \cdot c}{b}[/tex]

      [tex]$=\frac{\left(\frac{36}{x^{2}}+\frac{36}{x}\right)(x-3)}{36}[/tex]

Let us solve [tex]\frac{36}{x^{2}}+\frac{36}{x}[/tex].

Least common multiple of [tex]x^{2}, x[/tex] is [tex]x^{2}[/tex].

Make the denominator same based on the LCM.

So that multiply and divide the 2nd term by x, we get

[tex]$\frac{36}{x^{2}}+\frac{36}{x}=\frac{36}{x^{2}}+\frac{36 x}{x^{2}}[/tex]

              [tex]$=\frac{36+36 x}{x^{2}}[/tex]

Now, multiply by (x - 3).

[tex]$\frac{36+36 x}{x^{2}}(x-3)= \frac{(36 x+36)(x-3)}{x^{2}}[/tex]

[tex]$\frac{\left(\frac{36}{x^{2}}+\frac{36}{x}\right)(x-3)}{36}=\frac{\frac{(36 x+36)(x-3)}{x^{2}}}{36}[/tex]

Apply the fraction rule: [tex]\frac{\frac{b}{c}}{a}=\frac{b}{c \cdot a}[/tex]

                            [tex]$=\frac{(36x+36)(x-3)}{x^{2} \cdot 36}[/tex]

                            [tex]$=\frac{36(x+1)(x-3)}{x^{2} \cdot 36}[/tex]

Cancel the common factor 36.

                            [tex]$=\frac{(x+1)(x-3)}{x^{2}}[/tex]

Hence the solution is [tex]\frac{(x+1)(x-3)}{x^{2}}[/tex].

ACCESS MORE